2016
DOI: 10.1186/s13075-016-1168-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complement biomarkers in systemic sclerosis indicates a distinct pattern in scleroderma renal crisis

Abstract: BackgroundThe complement system has been implicated in pathogenesis of systemic sclerosis (SSc). The goal of the present study was to evaluate improved complement biomarkers in SSc.MethodsThe presence of C4d, reflecting activation of the classical/lectin pathways, C3bBbP corresponding to activation of the alternative pathway, and soluble terminal complement complexes (all complement pathways), was measured in plasma samples by enzyme-linked immunosorbent assay and correlated to clinical parameters. The study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
1
38
0
3
Order By: Relevance
“… 38 Very recently, a Swedish study demonstrated that patients with SRC had lower levels of C3 and factor B secondary to over-activation of the alternative pathway. 39 However, the serum levels of sTCC were lower in subjects with SRC. 39 This is a confounding finding given that one would expect to find increased levels during the initial stages of the acute phase of the renal crisis.…”
Section: Introductionmentioning
confidence: 95%
“… 38 Very recently, a Swedish study demonstrated that patients with SRC had lower levels of C3 and factor B secondary to over-activation of the alternative pathway. 39 However, the serum levels of sTCC were lower in subjects with SRC. 39 This is a confounding finding given that one would expect to find increased levels during the initial stages of the acute phase of the renal crisis.…”
Section: Introductionmentioning
confidence: 95%
“…In patients with LN, local immune complexes may be responsible for PTC C4d deposition as EDDs along the basement membrane of PTC were identified in 24/31 (77.4%) of patients with LN presenting PTC C4d deposition, whereas none of the patients with acute antibody-mediated rejection exhibited deposition(Li et al, 2007). In addition to autoantibodies, local shear stress on endothelial cells may play a role in the renal crisis in patients with scleroderma(Okroj et al, 2016;Yin et al, 2008), and PTC C4d correlated with an increased risk of renal failure(Batal et al, 2009). In our study, PTC C4d deposition was identified in 12 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Преднизолон per os 1 мг/кг/сут максимум 80 мг + ММФ (1,5-3 г/сут) -6 месяцев или пульс-терапия ЦФ 500 мг в/в каждые 2 недели 3 месяца; пульс-терапия МП 0,75 г в/в 3 дняв начале терапии или ЦФ per os 1-1,5 мг/кг/сут, максимум 150 мг/сут - Результаты последних исследований демонстрируют, что гемодиализ требуется половине пациентов с СПК либо из-за перегрузки объемом вследствие снижения почечной функции или для контроля артериального давления при резистентной АГ [74]. При оптимальной терапии возможно прервать диализ у 16-55 % больных с СПК.…”
Section: индукционная терапияunclassified
“…4, 2018 Погляд на проблему / Looking at the Рroblem является основной причиной гемодиализа и смерти у пациентов с РА [58]. Почечный амилоидоз при РА, обычно представленный АА-амилоидозом, возникает у пациентов с высокой активностью артрита, с длительным анамнезом и деструктивным по-Погляд на проблему / Looking at the Рroblem микроангиопатией, развитием неврологической симптоматики[74]. Группой экспертов Международного общества по изучению склеродермического почечного криза (ISRCS)[76] предложено диагностировать гипертензивный вариант СПК при наличии следующих критериев.…”
unclassified